Penggunaan Media Wayang Tokoh Untuk Meningkatkan Keterampilan Menceritakan Kembali Pada Materi Fabel - Shalaisa Saputri; Elsa Aulia Fadhilah (Politeknik Kampar, 2024)
The difficulty some students have in expressing their ideas can be a challenge for teachers. Not only improving their literacy but in forming effective communication skills. The use of wayang character media can be an innovative learning strategy to improve skills in retelling the content of fable stories. The aim of this research is to determine the use of wayang character media as an effort to improve skills in retelling the contents of fables. This research uses the literature study method. Literature study can be interpreted as a series of activities to collect data from literature, read, record and manage the results from various literature references. The results of this research show that the wayang character media can help students improve their skills in retelling the content of the fables they have listened to. Through the media of wayang figures, interesting and interactive learning situations are formed, both between students and the interaction between students and teachers. The enthusiastic side of the lower class students was also seen because they saw the attractive and funny shapes. Apart from that, students can take the message from the fable.